On the Obligation to Provide Environmental Information in the 21st Century – Empirical Evidence from Germany - Philipp Massier; Daniel Römer (University of Heidelberg, Department of Economics, 2012)
In this paper, we study the effectiveness of environmental information disclosure as a regulatory instrument. In particular we analyze its impact when environmental regulation is already advanced. Using German stock market data, we are able to identify the impact of the European Pollutant Emission Register (EPER) on the market value of listed firms using a Multivariate Regression Model (MVRM). First, we show that the publication of EPER data leads to negative abnormal returns of the respective listed firms in Germany. Second, we study drivers of these abnormal returns. Here, we find that the firms' individual level of non-carbon emissions can explain the observed changes in market valuation, while carbon dioxide emissions do not seem to be punished by the market. Moreover, we include information on voluntarily provided environmental reports and find that these reports can serve as a substitute to the obligatory register.
urn:nbn:de:bsz:16-opus-131697
Keywords: L51; Q52; G14; 330; information disclosure; EPER; event study; environmental reports; Umweltbericht; Unternehmenspublizität; Wirkungsanalyse; Börsenkurs; Ereignisstudie; Deutschland